Distribusi Coliform dan Escherichia Coli dari Beberapa Sungai Di Provinsi Bengkulu - Sipriyadi, Sipriyadi; Putra, Apriza Hongko; Lestari, Dian Pita (ORGANISMS: JOURNAL OF BIOSCIENCES, 2021)
The rate of decline in water quality in several rivers in Bengkulu province is thought to be a factor in the loss of several fish species in several rivers in Bengkulu. This study aims to calculate the amount of Coliform bacterial contamination and total coli in the river which is the habitat of fish in Bengkulu. This research was conducted by taking water samples from several rivers in Bengkulu province, including: Muar River (Muko-Muko Regency), Lubuk Banyau River and Air Nokan (North Bengkulu Regency), Alas River (Seluma Regency), Kedurang River and Air Nipis (South Bengkulu Regency), Padang Guci River and Muara Kinal (Kaur Regency). The samples that have been taken are then measured for total coliform and E. coli using the Most Probable Number (NPM) method. While the Abiotic factors include: Temperature, pH, Chemical Oxidase Demand (COD), Biological Oxidase Demand (BOD), and coordinate points. The total coliform test results showed that 8 rivers contaminated with E. coli were below the class II water quality standard (5000/100mL). There are 4 rivers contaminated with fecal coliform but still below the river water quality standard group II (1000/100 mL); MRH )43/100 mL), LBY (39/100mL), LKN (10/100mL), KDR (249/100 mL), NPS (157/100 mL), KNL (10/100mL), PGC (91/100 mL), and MRS (69/100 mL). Abiotic factor data shows a temperature range between 25 0 C (in NPS) to 28 0C (in LKN). The DO concentration range is 6.32 (LKN) to 7.99 (ARM). The results of the study can be concluded based on biotic data (coliform and total coli) and abiotic factors that 8 rivers are of good quality.AbstrakLaju penurunan kualitas Air di beberapa sungai di provinsi Bengkulu diduga akan menjadi faktor kehilangan beberapa spesies ikan di beberapa Sungai di Bengkulu. Penelitian ini bertujuan untuk menghitung jumlah cemaran bakteri Coliform dan total coli pada Sungai yang menjadi habitat ikan di Bengkulu. Penelitian ini dilakukan dengan cara mengambil sampel air dari beberapa sungai di provinsi Bengkulu, meliputi: sungai Muar (Kabupaten Muko-Muko), Sungai Lubuk Banyau dan Air Nokan (Kabupaten Bengkulu Utara), Sungai Alas (Kabupaten Seluma), Sungai Kedurang dan Air Nipis (Kabupaten Bengkulu Selatan), Sungai Padang Guci dan Muara Kinal (Kabupaten Kaur). Sampel yang telah diambil, lalu dilakukan pengukuran total coliform, dan E. coli dengan metode Most Probable Number (NPM). Sedangkan faktor Abiotik meliputi: Suhu, pH, Chemical Oxidase Demand (COD), Biological oxidase Demand (BOD), dan titik kordinat. Hasil uji Total coliform menunjukkan bahwa 8 sungai tercemar E. coli di bawah baku mutu air kelas II (5000 / 100mL). Terdapat 4 sungai yang tercemar fecal coliform namun masih dibawah baku mutu air sungai golongan II (1000/100 mL); MRH )43/100 mL), LBY (39/100mL), LKN (10/100mL), KDR (249/100 mL), NPS (157/100 mL), KNL (10/100mL), PGC (91/100 mL), dan MRS (69/100 mL). Data faktor abiotik menunjukkan kisaran suhu antara 25 0 C (di NPS) sampai 28 0C (di LKN). Rentang Konsentrasi DO mencapai 6,32 (LKN) hingga 7,99 (ARM). Hasil penelitian dapat disimpulkan berdasarkan data biotik (coliform dan total coli) dan faktor abiotik bahwa 8 sungai tergolong berkualitas baik.